2000
DOI: 10.1046/j.1365-2036.2000.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a multistep strategy for Helicobacter pylori eradication

Abstract: Since the human pathogen Helicobacter pylori was recognized as the most important aetiologic agent of chronic gastritis and as a major factor for peptic ulcer pathogenesis, the therapeutic approach to these common diseases has completely changed. 1 It has been well documented that H. pylori eradication not only heals duodenal ulcers, but also results in a marked decrease of peptic ulcer recurrence. 2 Despite the importance of H. pylori eradication in the management of a variety of upper gastrointestinal tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…Thus, as represented in Figure 2, it can be concluded that H. pylori eradication can finally be achieved in almost 100% of the patients if three 'rescue' therapies are consecutively given [Rokkas et al 2009;Gisbert et al 2008bGisbert et al , 2004Qasim et al 2005;Vicente et al 2002;Treiber et al 2002a;Beales, 2001;Zullo et al 2001a;Chan et al 2000;Seppala et al 2000;Gasbarrini et al 2000a;Gomollon et al 2000a].…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as represented in Figure 2, it can be concluded that H. pylori eradication can finally be achieved in almost 100% of the patients if three 'rescue' therapies are consecutively given [Rokkas et al 2009;Gisbert et al 2008bGisbert et al , 2004Qasim et al 2005;Vicente et al 2002;Treiber et al 2002a;Beales, 2001;Zullo et al 2001a;Chan et al 2000;Seppala et al 2000;Gasbarrini et al 2000a;Gomollon et al 2000a].…”
Section: Authormentioning
confidence: 99%
“…For example, in the study by Gasbarrini et al [2000a], a total of 2606 patients were administered a PPI, tinidazole and clarithromycin for 1 week. Patients with continuing infection were then given a second 1-week course of amoxicillin, clarithromycin and RBC.…”
Section: Authormentioning
confidence: 99%
“…Only four observational noncomparative studies including 283 patients reported the mean cure rates of SGT in third-line therapy [Cammarota et al 2004;Gasbarrini et al 2000;Liou et al 2013;Vicente et al 2002]. In addition, two noncontrolled studies [Fiorini et al 2013;Tay et al 2012] and one controlled nonrandomized study [Yahav et al 2006] reported cure rates of SGT mixing patients with second and third-line treatment.…”
Section: Studies Included Reporting Cure Rates Of Sgt In Third-line Tmentioning
confidence: 99%
“…Thus, as represented in Figure 2, it can be concluded that H pylori eradication can finally be achieved in almost 100% of the patients if three rescue therapies are consecutively given [72,76,140,141,[144][145][146]150,156,185,188] . Furthermore, these encouraging (cumulative) results have been obtained when more than three consecutive treatments have been prescribed [21] .…”
Section: Consecutive Eradication Treatmentsmentioning
confidence: 99%
“…For example, in the study by Gasbarrini et al [188] , a total of 2606 patients were administered a PPI, tinidazole and clarithromycin for 1 wk. Patients with continuing infection were then given a second 1-wk course of amoxicillin, clarithromycin and RBC.…”
Section: Consecutive Eradication Treatmentsmentioning
confidence: 99%